2020
DOI: 10.1080/01694243.2020.1861859
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid and adhesively bonded joints with dissimilar adherends: a critical review

Abstract: This paper reviews the reported literature on dissimilar (non-matched adherend) adhesively bonded joints (ABJs), currently used bonding processes, and the mechanisms by which these types of joints fail when subjected to structural loading and environmental conditions. Additionally, approaches to improve the performance of dissimilar ABJs, through geometrical and material modifications, are also discussed. Many studies have reported on the strength and failure behaviours of adhesively bonded joints, but of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 201 publications
(199 reference statements)
0
13
0
Order By: Relevance
“…Therefore, it can be concluded, that the critical energy release rate G IC in the cohesive material model was found to be the most influencing parameter on the force-displacement behavior in the simulation. The parameter for normal cohesive strength T changes the force in a minor extent but has a significant influence on the model stability and the amount of plastic deformation in the polymer core as already observed in [22]. The normal cohesive stiffness influences only the model stability.…”
Section: Discussion On Numerical-experimental Recalibrationmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, it can be concluded, that the critical energy release rate G IC in the cohesive material model was found to be the most influencing parameter on the force-displacement behavior in the simulation. The parameter for normal cohesive strength T changes the force in a minor extent but has a significant influence on the model stability and the amount of plastic deformation in the polymer core as already observed in [22]. The normal cohesive stiffness influences only the model stability.…”
Section: Discussion On Numerical-experimental Recalibrationmentioning
confidence: 69%
“…For the joining of steel-epoxy laminates, the authors can successfully apply the compliance method, but hardly any plastic deformation occurred here, and this is not to be expected for viscoplastic thermoplastics [21]. In [22], it was reported that the greater plastic deformation capacity of a ductile material leads to redistribution of load, so the application of the equation based on the modified compliance methods is open. Therefore, advanced measurement technology is required to determine the crack propagation experimentally and compare it with the simulation results [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with the rapid development of high-strength adhesive, adhesive bonding can provide higher load bearing efficiency compared with mechanical joints, resulting in the dissimilar materials adhesively bonded structures being continuously applied in various engineering fields as shown in Figure 1. [1][2][3][4][5][6] However, fracture is one of the most important failure modes of adhesively bonded structures and often leads to catastrophic consequences. From the point of design, the understanding of fracture characteristic plays a key role in the reliable design of adhesively bonded structures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Moreover, the application of fiber-reinforced composites leads to composite-metal adhesively bonded joints being adopted in engineering structure. [5][6][7][8] However, fracture of the adhesively bonded structures often leads to catastrophic failure. Based on this, the focus of the design of compositemetal adhesively bonded structures is the fracture of the bi-material interface.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high‐strength adhesive, adhesive joints are widely adopted in engineering structures (especially lightweight systems) to replace the traditional mechanical joints due to their high load transfer efficiency and uniform stress distribution 1–4 . Moreover, the application of fiber‐reinforced composites leads to composite‐metal adhesively bonded joints being adopted in engineering structure 5–8 . However, fracture of the adhesively bonded structures often leads to catastrophic failure.…”
Section: Introductionmentioning
confidence: 99%